Development of robust participation strategies for an aggregator of electric vehicles in multiple types of electricity markets. Issue 2 (27th October 2020) - Liu, Weijia; Wen, Fushuan; Dong, Zhaoyang; Palu, Ivo
Abstract: The flexible charging and discharging behaviours of electric vehicles (EVs) can provide a promising profit opportunity for EV owners or aggregators in deregulated market. However, a major barrier to overcome is the uncertain market prices. In this context, this study aims to establish a novel and robust model for EV aggregators to optimally participate in multiple types of electricity markets while considering the uncertainty of the prices in various markets. First, the electricity market framework and the obligation of an EV aggregator are introduced, and each EVaggregator is entitled to participate in day‐ahead, real‐time, and regulation service markets. To cope with forecasting errors of market prices and other uncertainties, a robust optimisation model is developed to schedule the charging/discharging of EVs in different markets. A stepwise bidding strategy is then proposed to formulate robust market bids, offering more flexibility in handling volatile market prices in actual electricity markets. After the clearing of multiple types of electricity markets, a real‐time dispatch model for EV aggregators is proposed for allocating the settlements and regulation orders to each EV. Finally, scenario‐based simulation is employed to demonstrate the effectiveness of the proposed bidding strategy using actual market data and regulation signals.